A novel prosumer-centric approach for social welfare maximization considering network voltage constraints in peer-to-peer energy markets. (May 2023) - Umer, Khalid; Huang, Qi; Khorasany, Mohsen; Amin, Waqas; Afzal, Muhammad
Abstract: With the increase of prosumers having distributed energy resources in peer-to-peer markets, the network voltages may not remain within safe operating levels. Therefore, any peer-to-peer energy trading scheme must also take technical constraints into consideration in addition to economic benefits. This paper proposes a two-stage social welfare maximization approach which also includes network voltage management. A novel concept of limit trading has been introduced to enhance the value prosumers extract from peer-to-peer energy trading. The simplicity and prosumer-centric nature of this concept makes it quite practical for such trading scenarios. The proposed approach has been tested on IEEE-14 bus network and has been compared to two other approaches in three practical scenarios. The results show that it can improve the total social welfare of the community by up to 10 % without causing voltage issues. Moreover, the proposed approach performs better as compared to other methods in indices like Power Export Index and Jain's Fairness Index. Highlights: A two-stage approach for community's social welfare maximization considering network voltage constraints is proposed. A novel prosumer-centric concept of limit trading has been introduced to enhance the value prosumers get from P2P trading. The comparison of the approach with two other methods shows that it performs better in social welfare index, power export index and Jain's fairness index.